Lessons learned to improve engagement, recruitment and retention of multilingual communities: a case study of a fresh produce box program - Yi, Stella S.; Hade, Erinn M.; Đoàn, Lan N.; Chan, Sze Wan; Kwon, Simona C. (Frontiers in Public Health, 2025)
Many communities are oftentimes labeled as “hard to reach communities” by health researchers. Instead, what may be a more appropriate framing is that conventional research approaches are a mismatch for recruiting and retaining these understudied communities. This paper describes an inclusive research process with particular attention to engaging multilingual communities in the U.S. that we have developed while implementing a community-level nutrition program. The program, Harvest Share, is an equity-centered, systems-based strategy to improve diet for neighborhood residents in Brooklyn, NY. Our research approach involves three components: participatory mapping, cultural adaptation/transcreation and language justice, and two cross-cutting areas: researcher positionality and research team diversity. The application of these methods in research resulted in our research program being highly accepted by partner organizations and participants. Applying inclusive research practices in addition to centering the community/es of interest will aid in the implementation of solutions that are feasible and culturally and linguistically responsive, ensuring successful recruitment and retention; and in the long run, sustainable, community-engaged solutions that have high acceptability and promote community well-being.